C3 glomerulonephritis disguised as Postinfectious GN - Lança,Alice (2018)
It is not uncommon for atypical cases of postinfectious glomerulonephritis (PIGN) to be confused with C3 glomerulonephritis (C3GN) due to considerable overlap of their clinical and histopathological features. We present a case of a 42-year-old man who was hospitalized with hematuria and worsening renal function after an episode of pharyngitis. Following a complete negative serological examination, the indolent clinical course associated with the findings of diffuse proliferative and exudative glomerulonephritis with dominant C3 staining and subendothelial and mesangial electron-dense deposits on the kidney biopsy were fundamental for the final diagnosis. The genetic test identified two mutations involved in the alternative complement pathway. Steroids and mycophenolate mofetil were initiated with improved renal function. This case alerts us that the presence of atypical clinical or histological features of apparent PIGN should raise suspicion of C3 glomerulopathy (C3G) because only a correct diagnosis will allow adequate treatment and a better long-term prognosis